Hadith #3680 - Sunan Abi Dawud - Da'ud bin Bakr bin Aby داود بن بكر بن أبي; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Every intoxicant is khamr (wine) and every intoxicant is forbidden. If anyone drinks wine, Allah will not accept prayer from him for forty days, but if he repents, Allah will accept his repentance. If he repeats it a fourth time, it is binding on Allah that He will give him tinat al-khabal to drink. He was asked: What is tinat al-khabal, Messenger of Allah? He replied: Discharge of wounds, flowing from the inhabitants of Hell. If anyone serves it to a minor who
Grade: Sahih